IMPLEMENTASI METODE COOPERATIVE LEARNING PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS XI DI SMK KESEHATAN BAKTI NUSANTARA - Riyan Susanti; Pondra Muliawan; Mar’atus Nur Sholehah (TSURAYYA: Journal Education, Economy and Religia, 2026)
Islamic Religious Education (PAI) plays a crucial role in shaping students' character, particularly at Bakti Nusantara Health Vocational School. Islamic Religious Education (PAI) at this school uses the Independent Curriculum, which allows teachers the freedom to adapt learning to suit their students' characteristics. Although the lecture method is still used, this method is often ineffective in maintaining student attention and participation. Therefore, Cooperative Learning methods are implemented, specifically the Group Investigation method, to increase student engagement and understanding of Islamic Religious Education (PAI) material. This study aims to explore the application of Cooperative Learning methods in Islamic Religious Education (PAI) learning and its impact on student motivation and understanding of the material. This study used a qualitative descriptive approach through in-depth interviews, observation, and documentation. The results showed that the Cooperative Learning method successfully increased student engagement in learning. Students were more involved in discussions, sharing knowledge, and completing assignments together, which can deepen their understanding of religious values.